Efeito da adubação fosfata sobre o acúmulo de biomassa e teor de brix de duas variedades de cana-de-açúcar - Silva Cruz, Sihelio Julio; Costa de Oliveira, Silvia Sanielle; Silva Cruz, Simerio Carlos [UNESP]; Machado, Carla Gomes [UNESP]; Pereira, Rodrigo Gomes (Univ Fed Rural Semi-arido-ufersa, 2009)
The objective of this study was to evaluate the accumulation of matter, dry matter content of Brix and two varieties of sugar cane, influenced by the phosphorus cultivated on "Zona da Mata" region, State of Alagoas. The experiment, a factorial 2 x 6, was composed of two varieties of cane; RB867515 and RB92579 and six phosphorus levels: zero, 30, 60, 90, 120 and 150 kg ha(-1), with the source of the phosphorus triple superphosphate. Was also used nitrogen and potassium in doses equivalent to 100 and 200 kg ha(-1) and K, respectively. The soil of the experimental area was set to raise the base saturation to 60%. At the beginning of the first rainfall of the rainy season of 2006 was performed with micro fertilization in coverage, in doses equivalent to 6,0; 6,0 and 7,0 kg ha(-1) of Cu, Zn and Mn, respectively. Was The chemical control of weeds. Every month, from August to October 2006, samples were collected in the cane plant. There was initially the number of plants m(2), followed by weighing the material. It was subsequently withdrawn a subsample containing ten plants for weighing. After weighing the material was passed in horsemanship and homogenized, again drew up a sample of approximately 300g, leading them to forced ventilation oven at 65 degrees C, toobtain constant weight. Resulting in the production of natural (MN) and dry matter (DM). In July, we analyzed the levels of Brix% juice in the refractometer Brix. The average values of production of natural (MN), dry matter (DM) and contents of Brix% were subjected to analysis of variance and regression for variables. The accumulation of dry matter and were influenced by fertilization. The contents of Brix% in two varieties did not suffer significant influence of fertilization.

Objetivou-se, neste trabalho, avaliar o acúmulo de matéria natural, matéria seca e teor de Brix por duas variedades de cana-de-açúcar, influenciados pela adubação fosfatada na Região da Zona da Mata do Estado de Alagoas. O experimento, um fatorial 2 x 6, foi constituído de duas variedades de cana; RB867515 e RB92579, e seis doses de fósforo: zero, 30, 60, 90, 120 e 150 kg por ha, tendo como fonte de fósforo o superfosfato triplo. Utilizou-se também adubação nitrogenada e potássica em doses equivalentes a 100 e 200 kg ha-1 de N e K, respectivamente. O solo da área experimental recebeu calagem para elevar a saturação por bases a 60%. No início das primeiras precipitações do período chuvoso de 2006 foi realizada a adubação com micronutrientes em cobertura, em doses equivalentes a 6,0; 6,0 e 7,0 kg ha-1 de Cu, Mn e Zn, respectivamente. Adotou-se o controle químico de plantas daninhas. Mensalmente, no período de agosto a outubro de 2006, foram realizadas as amostragens na cana-planta. Procedendo-se inicialmente a contagem do número de plantas por metro linear, seguido da pesagem do material. Posteriormente, foi retirada uma subamostra contendo dez plantas para pesagem. Após pesagem o material foi passado em picadeira e homogeneizado, novamente retirou-se uma subamostra de aproximadamente 300g, levando-as à estufa de ventilação forçada a 65ºC, até a obtenção de peso constante. Obtendo-se a produção de matéria natural (MN) e matéria seca (MS). No mês de julho, foram analisados os teores de Brix % caldo, em refratômetro de Brix. Os valores médios de produção de matéria natural (MN), matéria seca (MS) e teores de Brix % foram submetidos à análise de variância e regressão para as variáveis estudadas. Os acúmulos de matéria natural e matéria seca foram influenciados pela adubação fosfatada. Os teores de Brix % nas duas variedades não sofreram influência significativa da adubação fosfatada.
Effect of phosphate fertilization on the accumulation of biomass and brix content of two varieties of sugar cane
Keywords: Phosphate fertilization; accumulation of biomass; content of Brix